Clinical efficacy of dietary supplement Cartilox in osteoarthritis - I. S. Dydykina; P. S. Kovalenko; L. V. Menshikova (Научно-практическая ревматология)
The paper discusses the results and substantiates the effectiveness of pharmacotherapy for osteoarthritis of the knee joints using a dietary supplement Cartilox, which includes five active substances (type II collagen peptide, Boswellia serrata extract, curcuminoids, piperine and hyaluronic acid).